2004
DOI: 10.1152/ajpcell.00029.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isoform switching from SM-B to SM-A myosin results in decreased contractility and altered expression of thin filament regulatory proteins

Abstract: We previously generated an isoform-specific gene knockout mouse in which SM-B myosin is permanently replaced by SM-A myosin. In this study, we examined the effects of SM-B myosin loss on the contractile properties of vascular smooth muscle, specifically peripheral mesenteric vessels and aorta. The absence of SM-B myosin leads to decreased velocity of shortening and increased isometric force generation in mesenteric vessels. Surprisingly, the same changes occur in aorta, which contains little or no SM-B myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
6
32
0
Order By: Relevance
“…Thus, it is unlikely that compensatory mechanisms could have obscured the physiologic role of the deleted SMB in renal arterioles. Consequently, even in the absence of the highly active SMB isoenzyme, the physiologic function of afferent arterioles is maintained, which is in close agreement with the normal phenotype, organ functions, and life span of smb(−/−) mice [22,34]. Indeed, the presence of fast SMB or slow SMA isoforms in smooth muscle is not necessarily associated with a correspondingly fast or slow contraction of smooth muscle preparations [14,16,32,34,35], suggesting that other factors could well dominate the effects of alternatively 5 -spliced myosins.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, it is unlikely that compensatory mechanisms could have obscured the physiologic role of the deleted SMB in renal arterioles. Consequently, even in the absence of the highly active SMB isoenzyme, the physiologic function of afferent arterioles is maintained, which is in close agreement with the normal phenotype, organ functions, and life span of smb(−/−) mice [22,34]. Indeed, the presence of fast SMB or slow SMA isoforms in smooth muscle is not necessarily associated with a correspondingly fast or slow contraction of smooth muscle preparations [14,16,32,34,35], suggesting that other factors could well dominate the effects of alternatively 5 -spliced myosins.…”
Section: Discussionsupporting
confidence: 69%
“…However, alternatively 5 -spliced smooth muscle myosin isoforms (or any other myosin isoform) revealed large differences only in vitro [13,20,21] and in muscle in particular under unloaded conditions [22,31,33]. Investigating the force-velocity relationship of smooth muscle preparations with different amounts of SMB and SMA, however, revealed just marginal differences of shortening velocity under high load [31,34]. Since we investigated contractile parameters of our arterial preparations under pressure load in a physiologic range, a dominant modulatory role of alternatively 5 -spliced myosin isoforms on the regulation of contraction velocity could not be expected.…”
Section: Discussionmentioning
confidence: 99%
“…SM2 is not the only myosin isoform expressed in arteries, and studies by Sherwood and Eddinger (30) suggest that differences in SM2 expression do not correlate with changes in contractile function. Recent evidence (4,30) suggests that innervated arteries express more of another isoform of myosin, SM-B, and this isoform does affect contractile function (3,4). These data are consistent with innervated arteries being more differentiated for contractile function.…”
Section: Discussionmentioning
confidence: 56%
“…SMA and SMB isoforms differ by 7 aa in the S1 head region, and the SMB isoform containing the 7-aa insertion has higher myosin ATPase activity (9)(10)(11). By exon-specific gene targeting, we earlier reported that loss of SMB affects smooth muscle contractility and force velocity (12,13). In a similar manner, alternate splicing at the 3Ј end of the SMHC gene produces SM1 and SM2 isoforms; SM2 (200 kDa) contains a unique 9-aa sequence at the carboxyl terminus, whereas SM1 (204 kDa) has a 43-aa nonhelical tail region (5,7).…”
mentioning
confidence: 94%